Sierra Nevada amphibians demonstrate stable occupancy despite precipitation volatility in the early 21st Century - Halstead, Brian J.; Kleeman, Patrick M.; Rose, Jonathan P.; Fellers, Gary M. (Frontiers in Ecology and Evolution, 2023)
Climate can have a strong influence on species distributions, and amphibians with different life histories might be affected by annual variability in precipitation in different ways. The Sierra Nevada of California, USA, experienced some of the driest and wettest years on record in the early 21st Century, with variability in annual precipitation predicted to increase with climate change. We examined the relationship between adult occupancy dynamics of three high elevation anurans and site and annual variation in measures of winter severity, summer wetness, and cumulative drought. We further evaluated how these weather conditions affected the probability that each species would reproduce, conditional on their occurrence at a site. We found that although different aspects of weather affected the occupancy dynamics of each species differently, adult occupancy probabilities were generally stable throughout our 15-year study period. The probability of reproduction, although slightly more variable than adult occupancy, was similarly stable throughout the study. Although occurrence of the three species was resilient to recent extremes in precipitation, more detailed demographic study would inform the extent to which amphibian populations will remain resilient to increasing severity, duration, and frequency of drought and flood cycles.